2015
DOI: 10.1039/c4ra14176h
|View full text |Cite
|
Sign up to set email alerts
|

Water soluble blue-emitting AuAg alloy nanoparticles and fluorescent solid platforms for removal of dyes from water

Abstract: Chicken egg shell membrane, a naturally abundant protein membrane, was used to synthesize gold (Au), silver (Ag) and their bimetallic (AuAg) alloy nanoclusters at room temperature without the use of any reducing agent or catalyst. The as-formed gold and alloy clusters were highly fluorescent and exhibited intense blue emission around 435 AE 5 and 440 AE 5 nm, respectively. This is the first report confirming the formation of fluorescent alloy clusters exhibiting nanosecond lifetimes by a biomembrane-induced re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…A large number of processes are used for wastewater treatment such as chlorination, ozonation, adsorption, reverse osmosis, ultrafiltration, electrochemical process, advanced oxidation processes such as Fenton/photo-Fenton reactions, and photodegradation of dye molecules through photocatalysis, etc. In our previous studies, we have reported photocatalytic degradation process as a means for the removal of dyes from wastewater. However, among various processes available for water pollutants removal, adsorption is the most expedient and well-established method because of its ease, high efficiency, and low energy requirements. Various nanomaterials with specific morphology and structure have been extensively studied as adsorbents to remove organic dyes. In recent years, porous nanostructured metal oxides have been extensively used for wastewater treatment exhibiting interesting adsorption performance because of their high surface area, large surface-to-volume ratio, and available surface active sites for intimate contact with adsorbates. Adsorption of dyes onto the adsorbents occurs via electrostatic interaction, hydrogen bonding, coordination effect, surface/pore diffusion depending on the functional groups, surface properties, and morphological diversity of both dye and adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of processes are used for wastewater treatment such as chlorination, ozonation, adsorption, reverse osmosis, ultrafiltration, electrochemical process, advanced oxidation processes such as Fenton/photo-Fenton reactions, and photodegradation of dye molecules through photocatalysis, etc. In our previous studies, we have reported photocatalytic degradation process as a means for the removal of dyes from wastewater. However, among various processes available for water pollutants removal, adsorption is the most expedient and well-established method because of its ease, high efficiency, and low energy requirements. Various nanomaterials with specific morphology and structure have been extensively studied as adsorbents to remove organic dyes. In recent years, porous nanostructured metal oxides have been extensively used for wastewater treatment exhibiting interesting adsorption performance because of their high surface area, large surface-to-volume ratio, and available surface active sites for intimate contact with adsorbates. Adsorption of dyes onto the adsorbents occurs via electrostatic interaction, hydrogen bonding, coordination effect, surface/pore diffusion depending on the functional groups, surface properties, and morphological diversity of both dye and adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research demonstrated the formation of noble Au and Ag NCs based on the reductive ability of ESM itself in alkaline solution [ 43 , 45 , 46 ]. What about the in situ synthesis of Cu NCs employing ESM as the solid state platform?…”
Section: Resultsmentioning
confidence: 99%
“…Also, Devi reported the formation of Ag NPs by ESM [ 44 ]. Again, Pramanik proposed the formation of fluorescent AuAg alloy nanoparticles immobilized in solid ESM [ 45 ]. Nevertheless, to the best of our knowledge, the in situ synthesis of fluorescent Cu NCs embedded in monolithic ESM hasn’t been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Sarkar et al has applied adsorption as well as photodegradation using TiO 2 -Au nanocomposite for efficient removal of toxic dyes [8]. The success of the degradation of the pollutants using metal nanocrystals like Au, Ag, or Au-Ag, Cu etc has been demonstrated in large number of studies [7][8][9][10][11]. Studies also reveal that the catalytic efficiency may vary as the function of nature, size, shape, matrix of the nanocrystals [4,12].…”
Section: Introductionmentioning
confidence: 99%